Evaluation of long-term supplementation of a direct-fed microbial and enzymatically hydrolyzed yeast cell culture product on feedlot growth performance, efficiency of dietary net energy utilization, heat stress measures, and carcass characteristics in beef steers. Issue 1 (3rd February 2023) - Gubbels, Erin R; Rusche, Warren C; Block, Elliot; Rehberger, Tom; Thomson, Jesse S; Smith, Zachary K
Abstract: The objective of this research was to determine the influence of long-term supplementation (258 d) of a direct-fed microbial (DFM) and yeast cell wall (YCW) product used alone or in combination on growth performance, dietary net energy utilization, and carcass characteristics in beef steers finished under climatic conditions in the Northern Plains (NP). Single-sourced Charolais × Red Angus steers [ n = 256; body weight = 246 ± 1.68 kg] were blocked by pen location in a 2 × 2 factorial arrangement of DFM and YCW. Steers were administered a series of diets common to the NP and administered ractopamine hydrochloride (RH; 300 mg/kg) during the last 28 d of the finishing phase. Steers were vaccinated and poured at processing and individually weighed on days 1, 14, 42, 77, 105, 133, 161, 182, 230, and 258. Temperature–humidity index (THI) was calculated during RH supplementation. For 98% of the experiment, the THI was lower than 72 and thus cattle were not under high-ambient temperature. On days 1, 2, 21, and 22 of RH supplementation, respiration rates (RR), and panting scores (PS) were determined before and after AM and PM feedings (0700 h, 1100 h, 1400 h, and 1700 h). A DFM + YCW interaction was noted for the proportion of steers categorized as PS 2.0 at 1100 h on day 21 ( P = 0.03) and RR on day 21 at 1400 h ( P = 0.02). Control steers had a greater proportion of PS 2.0 compared to DFM or YCW steers ( P ≤ 0.05), while DFM + YCW steers did not differ from others ( P ≥ 0.05); DFM + YCW steers had greater ( P < 0.05) RR compared to DFM steers, while control and YCW steers did not differ from others ( P ≥ 0.05). No DFM + YCW interactions or main effects ( P ≥ 0.05) were observed for cumulative growth performance measures. However, YCW steers had 2% lower ( P = 0.04) dry matter intakes compared to steers not fed YCW. No DFM + YCW interactions or main effects ( P ≥ 0.05) were observed for carcass traits or liver abscess severity. However, a DFM + YCW interaction ( P < 0.05) was noted for the distribution of USDA yield grade (YG) 1 and Prime carcasses. Control steers had a greater proportion ( P < 0.05) of YG 1 carcasses compared to other treatments. DFM+YCW steers had a greater proportion ( P < 0.05) of USDA Prime carcasses compared to DFM or YCW but were similar to control steers, which were also similar to DFM or YCW. Overall, the use of DFM and YCW alone or in combination had minimal effects on growth performance, carcass traits, and heat stress measures in steers finished in NP climatic conditions.